PENGARUH PERSEPSI PENGUSAHA KECIL DALAM MENGGUNAKAN INFORMASI AKUNTANSI UNTUK MENYUSUN LAPORAN KEUANGAN (Studi Empiris Terhadap Pedagang Kecil Pasar Tradisional di Surakarta) - UNIBA, Trimurti (PARADIGMA, 2010)
The existing phenomena shows the financial administrative management of small-sized business in general is not professionally done, especially the reluctance of small entrepreneur to arrange their financial reports based on accounting information.  This qualitative descriptive research is aimed to investigate the small entrepreneur perception on accounting information use in arranging business financial report. The small entrepreneur perception consists of the perception on accounting information use, comparison of costs and benefits and also difficulty level in using the accounting information. One hundred and eighty small traders from twelve traditional markets in Surakarta have been taken as the sample in this research using purposive non-random sampling technique.Through regression and t-test approaches, the result of collected data analysis through questionaire dissemination to the respondents demonstrated that the small entrepreneur perception on accounting information use significantly influencing the willingness of small entrepreneurs to use accounting information to compile their business financial reports.  Keywords : Small Entrepreneur,Perception, Accounting Information, Financial Report